Analisis Manajemen Pembiayaan SMP Al-Irsyad Al-Islamiyah Pemalang - Abdul Rokhim; Adi Aliyan; Ara Hidayat (Universitas Pesantren Tinggi Darul 'Ulum, 2019)
This study aimed to obtain information konperehensip the empowerment of teachers and school principals in SMP Al-Irsyad Pemalang. This research is a qualitative descriptive penelitain. Source data is comprised of the principal, senior teachers, chairman of the committee, and students. Data collection procedures performed by observation and in-depth structured interviews, and documentation . Checking the validity of the findings made by the member check, the adequacy ofreference , and triangulate. The results of the following conclusions. Financial planning at the Junior High School Al-Irsyad Pemalang has done well by the ManagementTeam BOS school The planning of financing management in SMP Al-Irsyad Pemalang made during the preparation of Budget Plan School (RAPBS) with a preparationprocess performed by a team that already formed starting with EDS, involving allcomponents of the school in accordance with the instructions. The effectivenessof the financing in the Junior High School Al-Irsyad have are conducted effectivelyby involving teachers and school committees. Supervision of financing in theJunior High School Al-Irsyad conducted by relevant agencies as of the Inspectorateof the center and the regions, from the department.